Four new species of Serranochromis (Teleostei: Cichlidae) from the Cuanza and Okavango river systems in Angola, including a preliminary key for the genus - Stauffer, Jay R. Jr.; Bills, Roger; Skelton, Paul H. (Zootaxa, 2021)
The present study describes Serranochromis alvum n. sp., Serranochromis swartzi n. sp., Serranochromis cuanza n. sp., and Serranochromis cacuchi n. sp. from Angolan tributaries of the Cuanza and Okavango systems in Angola. The presence of four or five scale rows between the posterior margin of the orbit and the ascending arm of the preoperculum, the presence of widely set unicuspid teeth on the jaws, widely separated gill rakers, and anal fins with egg ocelli place these four species in Serranochromis. The Serranochromis described herein are distinguishable based on a combination of morphological and meristic characters, as well as pigmentation patterns. The interorbital width (14.3–15.9 % HL) of S. alvum is narrower than that of S. swartzi (17.6–19.8), S. cuanza (16.3–18.0), and S. cacuchi (20.0–21.7). Moreover, the interorbital width of S. cacuchi is greater than the other three described species. Serranochromis swartzi has a smaller preorbital depth (16.2–18.9 % HL) and snout length (29.6–31.9 % HL) than Serranochromis cuanza (PD 19.1–22.2, SNL 35.2–39.6 % HL). Serranochromis alvum is known only from the type locality at Cuito-Cuanavale at the junction of the Cuito and Cuanavale rivers, tributary to the Okavango River in Angola. Serranochromis swartzi is known only from the type locality in the Cuanza River, Angola. Serranochromis cuanza is restricted to the Cuanza River, below Capanda Dam, Angola, while S. cacuchi is known only from the Cacuchi River, a tributary of the Cuchi-Cubango River in Angola. The limited distribution of all four species and the absence of many congeners suggest, that in addition to previous studies that invoked a lacustrine speciation model, vicariance through drainage isolation seems to have played an important role in driving speciation in this group. The minimum polygon clusters that are formed when the first principal components of the meristic data are plotted against the second sheared principal components of the morphometric data show separation of the four new species.